Об одном варианте линеаризованной теории нестационарных краевых задач со свободной границей - Луковский, И.А.; Тимоха, А.Н. (Український математичний журнал, 1996)
Розглядаються принцип ліне арі за ції та отримані на його основі лінійні крайові задачі нелінійної теорії руху обмеженого об'єму рідини з вільною поверхнею, що знаходиться під впливом нестаціонарних вібраційних навантажень. Сформульовано та досліджено задачу про віброкапілярну форму рівноваги, спектральні проблеми теорії лінійних хвиль, проблеми стійкості (форм рівноваги, включаючи й задачу про біфуркації форм рівноваги. We analyze the principle of linearization and linear boundary-value problems obtained by using this principle in the nonlinear theory of motion for a bounded volume of liquid with free surface subjected to the action of a nonstationary oscillating load. We formulate and study the problem of vibrocapillary equilibrium state, spectral problems in the theory of linear waves, and problems of stability of equilibrium states, including the problem of bifurcation of equilibrium states.